2022
DOI: 10.3390/su14148246
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Asphalt Rejuvenation by Using Waste Tire Rubber Mixed with Waste Oils

Abstract: Waste materials such as waste tire rubber (WTR), waste cooking oil (WCO), bio-oils, waste engine oil (WEO), and other waste oils have been the subject of various scientific studies in the sustainable and waste research field. The current environmental concerns have been identified to protect natural resources and reuse waste materials. Accordingly, this work reviews the use of recycled waste tire rubber mixed with waste oils (waste cooking oil, waste engine oil) and bio-oils that can be extracted from waste oi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 113 publications
(274 reference statements)
0
2
0
Order By: Relevance
“…Cao et al [16] studied the regeneration effect of waste vegetable oil on aging asphalt, and the results showed that waste vegetable oil can not only improve the road performance of aging asphalt, but also ensure its safety performance and anti-aging performance. However, there is still a gap between the performance of a waste engine oil, recycled asphalt binder and new asphalt binder [17][18][19][20]. Therefore, some scholars began to modify the waste engine oil, recycled asphalt binder to improve its performance.…”
Section: Introductionmentioning
confidence: 99%
“…Cao et al [16] studied the regeneration effect of waste vegetable oil on aging asphalt, and the results showed that waste vegetable oil can not only improve the road performance of aging asphalt, but also ensure its safety performance and anti-aging performance. However, there is still a gap between the performance of a waste engine oil, recycled asphalt binder and new asphalt binder [17][18][19][20]. Therefore, some scholars began to modify the waste engine oil, recycled asphalt binder to improve its performance.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, scholars have attempted to pre-desulfurize CTR by using vegetable oil, waste edible oil, furfural oil, waste engine oil, etc. [2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%